المثول الفوري اجراء بديل للمتابعة في التلبس بالجنح في التشريع الجزائري - بن مالك أحمد (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2023)
The Algerian legislator adopted the violation of the Code of Criminal Procedure for the year 2015, a procedure Immediate appearance as an alternative to the flavoring system of misdeed The formal and objective conditions and the unique procedures before and during the trial. The penalties in some misdemeanors that do not require an eligibility, and this action is subject to a group of formal and objective conditions and unique procedures before and during the trial. This study seeks; To define legal and procedures for immediate appearance in Algerian legislation, its terms and controls, and this action works to strip the majestic and the whole Republic of the authority of the deposit is the mortgage of temporary imprisonment as an opponent in the lawsuit and entrusts this Ability to Judge only, and he also enabled the accused for the first time in Algeria to contact his lawyer Inside the corridors of the court before the session in a special place.